In vitro antioxidant activity of Lippia origanoides H.B.K (Research, Society and Development, 2021)
Oxidative stress is a constant threat to the body. As a result, a series of antioxidant defenses, in addition to cell repair systems, have evolved with the aim of protecting against destruction and damage caused by free radicals. Plants produce a huge variety of antioxidants that tend to act against cell damage by removing reactive oxygen species and reactive nitrogen species. Lippia origanoides Humboldt, Bonpland and Kunth, Verbenaceae family, is an aromatic shrub known as “Rosemary-do-campo”, being responsible for several pharmacological and biological activities, including antioxidant protection. This work aimed to analyze the chemical composition of the essential oil of L.origanoides HBK (OELO) and evaluate its antioxidant activity in vitro. Therefore, the in vitro antioxidant potential was evaluated by the reducing potential, 2,2diphenyl-1-picrylhydrazyl (DPPH), lipid peroxidation inhibition (TBARS), hydroxyl radical and nitric oxide methods, at concentrations of 100, 300 and 900 µM. All concentrations showed antioxidant activity. The reducing potential, reductions in TBARS production and inhibition of the DPPH• radical were superior to the positive control, ascorbic acid, showing a high presence of antioxidant substances. These results suggest that this species is promising for the production of herbal medicine where the antioxidant activity is of desired action.